The global financial crisis of 2008–2009: an opportunity for development studies? - Copestake, James (Journal of International Development, 2010)
This paper draws upon the five other papers presented in this volume, along with other presentations made at the 2009 Development Studies Association Conference, to reflect on the relationship between development studies and the 2008–2009 global financial crisis. It first analyses antecedents to the crisis by relating the papers presented by Gore (on long waves of capitalism) and Fischer (on China's integration into the world economy) to a Polanyian analysis. It then considers immediate policy responses with particular reference to India (based on the conference presentation by Mehrotra), China (based on the paper by de Haan) and the 2009 DFID White Paper. Third, it considers two possible additional sources of finance for developing countries: South Korean aid (discussed by Chun et al.) and new forms of international money (discussed by Hudson). The paper concludes that while the crisis is a reminder of structural global economic interconnectedness a challenge for development studies is to combine this fact with analysis that is also interdisciplinary, multi-tiered and policy relevant. Copyright © 2010 John Wiley & Sons, Ltd.
Development Studies
Keywords: 2009 DFID White Paper; China; capitalism; development economics; development studies; global financial crisis; international development; international economic integration

Power and Progress: The Swing of the Pendulum - Stewart, Frances (Journal of Human Development & Capabilities, 2010)
This paper uses Polanyi's 1944 analysis of policy change—in which there are long-term swings from state regulation to markets and back again, as the consequences of one regime lead to political reactions that in turn reverse the policies. It shows how the Polanyi analysis continued to apply throughout the twentieth and early-twenty-first century, well beyond when he wrote, and that the swings also apply to developing country policy-making. It argues that there are new signs of policy change—this time against market domination—in a number of developing countries. The paper concludes that Polanyi's view of the conditions behind policy change—notably long-term political movements, political struggle and political conflict—needs to be introduced into the analysis of policy change for the promotion of human development and the expansion of capabilities.
Development Studies; Economics
Keywords: developing countries; government policy; human development; legislation; policy sciences; policy swings; political economy; political planning

Le principe de réciprocité chez Karl Polanyi, contribution à une définition de l'économie solidaire - Servet, Jean-Michel (Revue Tiers Monde, 2010)
English translation: Karl POLANYI has an indirect understanding of the societies that were part of the Third World in the fifties. From anthropologists he came out with the principle of reciprocity. He then opposed this principle of economic integration to both redistribution and market principles. Reciprocity can neither be viewed as a practice of primitive societies (as in evolutionist approaches) nor as a gift and counter-gift exchange. Reciprocity needs to be understood as a social whole and through a claimed mutual dependency. In this approach, reciprocity allows to set up the definition of the solidarity-based economy. Jean-Michel Servet, “ Le principe de réciprocité chez Karl Polanyi, contribution à une définition de l'économie solidaire ”, Revue Tiers Monde 2/2007 (n° 190) , p. 255-273
Development Studies
Keywords: reciprocity